2020
DOI: 10.1002/cssc.202001243
|View full text |Cite
|
Sign up to set email alerts
|

Deep Eutectic Solvent Extraction of High‐Purity Lignin from a Corn Stover Hydrolysate

Abstract: A lactic acid/chlorine chloride‐based deep eutectic solvent (DES) was used for the extraction of high‐purity lignin (up to 94.7 %) in high yield (up to 75 %) from the hydrolysis/fermentation residue corn stover hydrolysate (CSH), which was generated from a pilot‐plant‐scale biorefinery. A range of extraction conditions were investigated, which involved varying reaction temperature, time, and DES composition. The relationship between lignin yield, purity, and structural characteristics with DES treatment condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 34 publications
(27 reference statements)
3
30
0
Order By: Relevance
“…Also, under the experimental conditions with a temperature of 393 K and a pretreatment time of 6 h, the pretreatment solvent was ChCl/lactic acid with a molar ratio of 1:2. The extraction rate and purity of lignin reached 79.4 and 94.2%, respectively. , Higher temperatures had a significant enhancement on the pretreatment effect of the low molar ratio of ChCl/lactic acid. The xylan removal rate increased from 38.2 to 75.4%, and the lignin extraction rate increased from 48.2 to 64.8% …”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Also, under the experimental conditions with a temperature of 393 K and a pretreatment time of 6 h, the pretreatment solvent was ChCl/lactic acid with a molar ratio of 1:2. The extraction rate and purity of lignin reached 79.4 and 94.2%, respectively. , Higher temperatures had a significant enhancement on the pretreatment effect of the low molar ratio of ChCl/lactic acid. The xylan removal rate increased from 38.2 to 75.4%, and the lignin extraction rate increased from 48.2 to 64.8% …”
Section: Resultsmentioning
confidence: 89%
“…The extraction rate and purity of lignin reached 79.4 and 94.2%, respectively. 38,41 Higher temperatures had a significant enhancement on the pretreatment effect of the low molar ratio of ChCl/lactic acid. The xylan removal rate increased from 38.2 to 75.4%, and the lignin extraction rate increased from 48.2 to 64.8%.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The simple synthetic process makes DESs more advantageous over ILs by avoiding the use of organic solvents and the generation of by-products. Thus, DESs have been considered as attractive alternatives to ILs in diverse applications, [6][7][8][9][10][11] such as separations, catalysis, fabrication of functional materials, and electrochemistry, etc. More importantly, the properties of DESs can be easily tuned by modifying the types and/or the ratio of the components.…”
mentioning
confidence: 99%
“…35 It was also reported that the hemicellulose-derived impurities were absent in DES lignin. 35,36 2.2.2. Preparation of PLA/Lignin Composites.…”
Section: Introductionmentioning
confidence: 95%
“…33,34 Hence, this method is a good technique to fractionate biomass into cellulose, as well as lignin, with high purity, reduced structural heterogeneity, and often low molecular weight along with reduced polydispersity. 35 Detailed investigations of the physicochemical properties of DES-extracted lignin were previously reported by the authors. 36 On the one hand, these physicochemical characteristics may position DES lignin as an attractive additive to polymers in the preparation of biocomposites.…”
Section: Introductionmentioning
confidence: 99%